The Effect of Confidence Rating on a Primary Visual Task - Bonder, Taly; Gopher, Daniel (Frontiers in Psychology, 2019)
The current study explored the influence of confidence rating on visual acuity. We used brief exposures of the Landolt gap discrimination task, probing the primary visual ability to detect contrast. During 200 practice trials, participants in the Confidence Rating group rated their response-confidence in each trial. A second (Time Delay) group received a short break at the end of each trial, equivalent to the average rating response time of the Confidence Rating group. The third (Standard Task) group performed the Landolt gap task in its original form. During practice, the Confidence Rating group developed an efficient monitoring ability indicated by a significant correlation between accuracy and confidence rating and a moderate calibration index score. Following practice, all groups performed 400 identical test trials of the standard Landolt gap task. In the test trials, the Confidence Rating group responded more accurately than the control groups, though it did not differ from them in response time for correct answers. Remarkably, the Confidence Rating group was significantly slower when making errors, compared the control groups. An interaction in learning efficiency occurred: the Confidence Rating group significantly improved its reaction times after the initial practice, as compared to both control groups. The findings demonstrate an effect of confidence rating on the formation of processing and response strategies, which granted participants significant benefits in later performance.